La educación intercultural bilingüe y la revitalización de la cultura del pueblo Otavalo :Estudio del caso en el CECIB Luis Ulpiano de la Torre - Cañarejo Cusin, María Nancy (2015)
Bilingual, intercultural education is the result of the struggles of indigenous nationalities and peoples of Ecuador, however, the goals and the purposes for which they were created has not had the expected results. Lack of education in accordance with reality and the absence of a distinct identity in Ecuadorian education in society has resulted in a reactionary attitude that has prevented the growth of this educational initiative; and, on the other hand, the existence of a cultural awareness of their own roots has impeded ample Development of intercultural education. All these situations can be corroborated in community of Canton Kotama Otavalo in Imbabura province, where, despite the existence of all possibilities in bilingual education, it has not been developed because the teachers are not risk taking in their obligation to the community and the country. While it is true that the Construction of the republic raises intercultural mainstreaming in all government policies, the present mental colonization in social, economic, political, educational, cultural and spiritual everyday life of our people has not permitted that the codes of the daily life of indigenous knowledge be included, but rather , rejects everything Indian . This situation is clearly evidenced in the Education Unit Luis Ulpiano De Torre community Kotama , CECIB in which all opportunities are provided, but the me mentioned multiculturalism is far from be experienced.